2023
DOI: 10.1007/s42452-023-05318-7
|View full text |Cite
|
Sign up to set email alerts
|

Relationship, importance, and development of analytical techniques: COD, BOD, and, TOC in water—An overview through time

Abstract: Analytical techniques to measure organic matter in water, such as Chemical Oxygen Demand (COD), Biochemical Oxygen Demand (BOD5), and Total Organic Carbon (TOC) are widely used. Modifications have been proposed to make them faster, more sensitive, and more environmentally friendly. The purpose of producing a review over some time is to show the changes made on the standardized methods of each of these techniques, and to highlight the relationship between them in the process of ascertaining organic matter in wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 84 publications
1
12
0
Order By: Relevance
“…The COD concentration exceeded the BOD concentration, which align with theoretical expectations. Both values indicate that the level of organic pollution in the wastewater [29]. The high COD and BOD concentrations are likely the result of microalgae decomposition.…”
Section: Changes In Wastewater Characteristicsmentioning
confidence: 96%
“…The COD concentration exceeded the BOD concentration, which align with theoretical expectations. Both values indicate that the level of organic pollution in the wastewater [29]. The high COD and BOD concentrations are likely the result of microalgae decomposition.…”
Section: Changes In Wastewater Characteristicsmentioning
confidence: 96%
“…Studies by (Aguilar-Torrejón et al, 2023), (Dubber et al, 2010), and (Jiang et al, 2018) have determined the correlation between TOC, COD and BOD5 for the control of organic water pollution. We studied the correlation between the concentrations of TOC, COD and BOD5 and the technological mode of operation of the RCWS of the Rivne NPP, which is determined by the concentration cycles φ (2).…”
Section: Correlation Between Parameters Related To Om Contentmentioning
confidence: 99%
“…The dynamics of changes in OM content and its water discharge can have signi cant impacts on aquatic ecosystems, water quality, and the overall health of the environment (Shi et al, 2019). Argue (Sadiq et al, 2022) suggested that natural inputs of OM to water bodies are due to their release by aquatic organisms through metabolism, leaching from catchment surfaces and desorption from sediments, while according to (Aguilar-Torrejón et al, 2023), anthropogenic sources of OM include discharges of OM with industrial and domestic water. The amount of water withdrawn and discharged to support the operation of RCWS determines the discharge of individual chemicals to a water body.…”
Section: Introductionmentioning
confidence: 99%
“…The organic carbon in water/wastewater originates from a variety of organic compounds in various oxidation states. Some of these carbon compounds can be oxidized through chemical or biological processes, and the routinely applied chemical oxygen demand (COD meas ) and biochemical oxygen demand (BOD) analyses are typically used to characterize these fractions [ 1 , 2 ]. COD meas measures the oxygen equivalent (mg O 2 dm −3 ) of the organic matter content of the sample, susceptible to oxidation by strong chemical oxidants (potassium permanganate or potassium dichromate) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…This standard method has a few disadvantages that limit its application, such as a long reflux time, expensive chemicals (Ag 2 SO 4 ), and toxic (K 2 Cr 2 O 7 , HgSO 4 ) and highly corrosive (H 2 SO 4 ) reagents. Nevertheless, this classic technique seems to be one of the frequently used COD measuring procedures in practice [ 2 ]. In a modified version of the method, the digestion takes place in a closed system, and spectrophotometry is used for analysis (the sealed-tube method).…”
Section: Introductionmentioning
confidence: 99%